Preparation, Modeling, and Optimization of Mechanical Properties of Epoxy/HIPS/Silica Hybrid Nanocomposite Using Combination of Central Composite Design and Genetic Algorithm. Part 1. Study of Damping and Tensile Strengths - Rostamiyan, Y.; Fereidoon, A.B. (Проблемы прочности, 2013)
Brittle nature and poor resistance in front of vibrational waves despite of good mechanical strength have limited widespread use of epoxy resins in industry. In current study a new combination of thermoplastic and particulate nanofiller is used as modifier to enhance simultaneously tensile strengths and damping properties in first and second modes of epoxy-based nanocomposite. High impact polystyrene (HIPS) as thermoplastic phase and silica nanoparticles as particulate phases incorporately used to obtain ternary epoxy-based nanocomposite. In current study solution blending as dispersion mechanism is used to prepare homogenous mixture and brings good molecular level of mixing. Tensile and damping properties in first and second modes were the two different mechanical tests investigated in order to achieve higher toughness strengths without attenuating desired mechanical properties. Also central composite design is employed to present mathematical models for predict mechanical behaviors of epoxy/HIPS/silica nanocomposite as function of physical factors. The effective parameters investigated were HIPS, SiO₂, and hardener contents. Based on mathematical functions obtained from central composite design model, the genetic algorithm as one of powerful optimization tools is applied to find optimum values of mentioned mechanical properties. From the results it can be found that combination of HIPS and silica nanoparticles significantly increased tensile and damping strengths of epoxy resin up to 69, 42, and 91%, respectively. The morphology of fracture surface is also studied by scanning electron microscopy Значительная хрупкость и низкие характеристики сопротивления волновым нагрузкам, несмотря на высокую механическую прочность, обусловили недостаточно широкое промышленное применение эпоксидных смол. В работе используется новое сочетание термопластичных и дисперсных нанонаполнителей в качестве модификатора для одновременного повышения прочности на разрыв и демпфирующих свойств нанокомпозита на эпоксидной основе при нагружении по первой и второй моде. Для получения трехкомпонентного нанокомпозита на эпоксидной основе используются ударопрочный полистирол в качестве термопластичной фазы и наночастицы из кремнезема в качестве дисперсной фазы. Для реализации дисперсионного механизма применяется метод перемешивания раствора для приготовления однородной смеси, обеспечивающий адекватное перемешивание на молекулярном уровне. Прочность на разрыв и демпфирующие свойства материала при его нагружении по первой и второй моде оценивали при проведении двух различных механических испытаний с целью достижения более высокой прочности и ударной вязкости без ухудшения требуемых механических свойств. При создании математических моделей для прогнозирования механического поведения нанокомпозита из эпоксидной смолы, ударопрочного полистирола и кремнезема как функции физических факторов используется центральный композиционный план. В качестве эффективных параметров исследовалось процентное содержание ударопрочного полистирола, кремнезема и эпоксидного отвердителя. На основе математических функций, полученных с помощью модели центрального композиционного плана, был использован генетический алгоритм, как одно из мощных средств оптимизации, для определения оптимальных значений механических свойств. Полученные результаты показывают, что сочетание наночастиц ударопрочного полистирола с кремнеземом значительно увеличивает предел прочности на разрыв и характеристики демпфирования эпоксидной смолы на 69, 42 и 91% соответственно. Морфологию поверхностей разрушения изучали с помощью сканирующего электронного микроскопа Значна крихкість і низькі характеристики опору хвильовій напрузі, незважаючи на високу механічну міцність, обумовили недостатньо широке промислове використання епоксидних смол. Використовується нове поєднання термопластичних і дисперсних наповнювачів як модифікатора для одночасного підвищення міцності на розрив і демпфірувальних властивостей нанокомпозита на епоксидній основі при навантаженні за першою і другою модою. Для отримання трикомпонентного нанокомпозита на епоксидній основі використовуються удароміцний полістирол як термопластична фаза і наночастинки з кремнезему як дисперсна фаза. Для реалізації дисперсійного механізму використовується метод перемішування розчину для приготування однорідної суміші, що забезпечує адекватне перемішування на молекулярному рівні. Міцність на розрив і демпфірувальні властивості матеріалу при його навантаженні за першою і другою модою оцінювали при проведенні двох різних механічних випробувань із метою досягнення більш високої міцності й ударної в’язкості без погіршення необхідних механічних властивостей. При розробці математичних моделей для прогнозування механічної поведінки нанокомпозита з епоксидної смоли, удароміцного полістирола і кремнезему як функції фізичних чинників використовується центральний композиційний план. За ефективні параметри брали процентний вміст удароміцного полістирола, кремнезему й епоксидного затверджувача. На основі математичних функцій, отриманих за допомогою моделі центрального композиційного плану, було використано генетичний алгоритм, як один із потужних засобів оптимізації, для визначення оптимальних значень механічних властивостей. Отримані результати свідчать, що поєднання наночастинок удароміцного полістирола з кремнеземом значно збільшує границю міцності на розрив і характеристики демпфірування епоксидної смоли на 69, 42 і 91% відповідно. Морфологію поверхонь руйнування вивчали за допомогою сканувального електронного мікроскопа.